Strength–ductility balance of powder metallurgy Ti–2Fe–2W alloy extruded at high-temperature - Abdollah Bahador; Ammarueda Issariyapat; Junko Umeda; Ridvan Yamanoglu; Catalin Pruncu; Astuty Amrin; Katsuyoshi Kondoh (Journal of Materials Research and Technology, 2021)
This study aims to improve the mechanical properties of a Ti–2Fe base alloy by adding W solute and performing hot extrusion at a high temperature (1000 °C). W was added at 0, 1, 2, and 3 wt% using the powder metallurgy route and homogenization heat treatment. The as-extruded materials predominantly consisted of α phase with different microstructure morphologies; Ti–2Fe and Ti–2Fe–1W contained equiaxed α grains, while Ti–2Fe–2W and Ti–2Fe–3W showed equiaxed + acicular and acicular shape, respectively. Effective grain refinement was obtained in Ti–2Fe–2W (average grain size: ~1.64 μm), which greatly contributed to the strengthening. The solid solution of W was studied with X-ray powder diffraction, where a proportional increment of β lattice constant occurred as the W solute increased in the matrix (Ti–Fe). Additionally, electron backscatter diffraction analysis revealed that the W solution reduced the intensity of the prismatic texture along the extrusion direction. Based on the experimental evaluations, extruded Ti–2Fe–2W alloy exhibited a maximum yield strength of 925 MPa with excellent elongation 30% at room temperature, indicating a remarkable trade-off in strength and ductility.